The anti-apoptotic proteins NAF-1 and iASPP interact to drive apoptosis in cancer cells. Issue 3 (29th November 2018) - Iosub-Amir, Anat; Bai, Fang; Sohn, Yang-Sung; Song, Luhua; Tamir, Sagi; Marjault, Henri-Baptiste; Mayer, Guy; Karmi, Ola; Jennings, Patricia A.; Mittler, Ron; Onuchic, José N.; Friedler, Assaf; et al.
Abstract : We reveal a novel interaction between the two anti-apoptotic proteins iASPP and NAF-1, which are overexpressed in many types of cancer cells, and propose that this interaction is required for apoptosis activation in cancer cells. A peptide derived from the interaction interface inhibits apoptosis in cells. Abstract : Suppression of apoptosis is a key Hallmark of cancer cells, and reactivation of apoptosis is a major avenue for cancer therapy. We reveal an interaction between the two anti-apoptotic proteins iASPP and NAF-1, which are overexpressed in many types of cancer cells and tumors. iASPP is an inhibitory member of the ASPP protein family, whereas NAF-1 belongs to the NEET 2Fe–2S protein family. We show that the two proteins are stimulated to interact in cells during apoptosis. Using peptide array screening and computational methods we mapped the interaction interfaces of both proteins to residues 764–778 of iASPP that bind to a surface groove of NAF-1. A peptide corresponding to the iASPP 764–780 sequence stabilized the NAF-1 cluster, inhibited NAF-1 interaction with iASPP, and inhibited staurosporine-induced apoptosis activation in human breast cancer, as well as in PC-3 prostate cancer cells in which p53 is inactive. The iASPP 764–780 IC50 value for inhibition of cell death in breast cancer cells was 13 ± 1 μM. The level of cell death inhibition by iASPP 764–780 was altered in breast cancer cells expressing different levels and/or variants of NAF-1, indicating that the peptide activity is associated with NAF-1 function. We propose that the interaction between iASPP and NAF-1 is required for apoptosis activation in cancer cells. This interaction uncovers a new layer in the highly complex regulation of cell death in cancer cells and opens new avenues of exploration into the development of novel anticancer drugs that reactivate apoptosis in malignant tumors.